Minimally invasive therapy of upside-down stomach: A single-center experience - Radek Vrba; Cestmir Neoral; Rene Aujesky; Martin Stasek; Linda Bebarova; Petr Janda; Tereza Vrbova; Tomas Bohanes; Katherine Vomackova; Martin Lovecek (Wolters Kluwer Medknow Publications, 2017)
Introduction: The aim of this study is to evaluate short-term and long-term outcomes of minimally invasive therapy in Type IV hiatal hernia (upside-down stomach). Patients and Methods: A retrospective study of 58 consecutively operated patients with Type IV hiatal hernia between 1998 and 2015 was conducted. Short-term outcome was evaluated using Clavien-Dindo classification and long-term outcomes using phone survey and subjective assessment of patients at least 1 year following surgery. Results: Laparoscopic hiatoplasty was performed in all patients, with gastropexy in 55.2%, fundoplication in 39.6%, and combination of fundoplication and gastropexy in 5.2%. Complications were observed in 6.9%. Two early reoperations (within 30 days) due to acute reherniation were necessary. Adverse events occurred in seven cases - pleural opening and peroperative bleeding. Three patients were reoperated laparoscopically 2-17 months after the first surgery due to receiving partial stomach herniation. In 67.2% of patients, long-term subjective quality of life assessment was available. Eighty percent of them were completely satisfied, without recurrence of preoperative symptoms. Conclusion: Elective laparoscopic surgery of hiatal hernia Type IV is a safe procedure, which has all the benefits of minimally invasive therapy with favorable short- and long-term results.